SINKRONISASI PROGRAM PEMANFAATAN RUANG (SPPR) KOTA TANJUNGPINANG DALAM MENDUKUNG PENYUSUNAN PRIORITAS PROGRAM PEMBANGUNAN DAERAH - Weldy Anugra Riawan (JURNAL PELITA KOTA, 2022)
According to mandate of Government Regulation Number 21 of 2021 concerning the Implementation of Spatial Planning, the Regional Government needs to synchronize the spatial utilization program (SPPR) with reference to the synchronization of programs that have been carried out by the Government. The output of these activities can be used as input in the preparation of the Regional Government Work Plan and also in the vision and mission of the Regional Head and RPJMD. The implementation of integrated infrastructure development in Tanjungpinang City is still experiencing various problems, including the lack of focus on regional targets that will be driven by infrastructure development, the synergism of infrastructure development programs between Regional Apparatus Organizations (OPD) within the Tanjungpinang City Government and the ineffectiveness of the infrastructure development budgeting system. To overcome these various problems, it is necessary to synchronize the annual/short-term space utilization program which is an integration document between the Tanjungpinang City regional development plan in 2023 and the spatial plan as the basis for compiling an infrastructure development plan for OPD in accordance with the Tanjungpinang City RTRW document. This is done so that the focus of regional targets and the synergy of infrastructure development programs can be achieved. Keywords: SPPR; Tanjungpinang City Development Plan; Tanjungpinang City RTRW Abstrak Sesuai amanat Peraturan Pemerintah Nomor 21 tahun 2021 tentang Penyelenggaraan Penataan Ruang bahwa Pemerintah Daerah perlu melakukan sinkronisasi program pemanfaatan ruang (SPPR) dengan mengacu sinkronisasi program yang telah dilakukan oleh Pemerintah. Output kegiatan tersebut dapat menjadi masukan dalam penyusunan Rencana Kerja Pemerintah Daerah dan menjadi masukan dalam penyusunan visi misi Kepala Daerah dan RPJMD. Pelaksanaan keterpaduan pembangunan infrastruktur di Kota Tanjungpinang masih mengalami berbagai permasalahan antara lain belum fokusnya sasaran kewilayahan yang akan didorong pembangunan infrastrukturnya, belum sinergisnya program pembangunan infrastruktur antar Organisasi Perangkat Daerah (OPD) di lingkungan Pemerintah Kota Tanjungpinang serta belum efektifnya sistem penganggaran pembangunan infrastruktur. Untuk mengatasi berbagai masalah tersebut, maka perlu dilakukan sinkronisasi program pemanfaatan ruang tahunan/jangka pendek yang merupakan dokumen integrasi antara rencana pembangunan daerah Kota Tanjungpinang Tahun 2023 mendatang dengan rencana spasial sebagai dasar penyusunan rencana pembangunan infrastruktur bagi OPD agar sesuai dengan dokumen RTRW Kota Tanjungpinang. Hal ini dilakukan agar fokus sasaran kewilayahan dan sinergitas program pembangunan infrastruktur dapat tercapai. Kata Kunci: SPPR, Rencana Pembangunan Kota Tanjungpinang, RTRW Kota Tanjungpinang